Avaliação dos parâmetros hematológico e bioquímicos de codornas japonesas (Coturnix coturnix japonica) em diferentes faixas etáriass - Bernardino, Maria das Graças da Silva (2016)
The Japanese quail industry is increasing in expansion in Brazil and has become a very important activity in the Brazilian economic scenario, so it has been generated jobs and income for the population. However, it notes a lack of knowledge about blood and biochemical constituents of the specie. Thus, the study aimed to evaluate the influence of age on hematological and biochemical parameters of Japanese quail (Coturnix coturnix japonica). Seven samples were collected with quail at 7, 14, 21, 28, 35, 42 and 80 days old. In total, 224 quail were evaluated wherever 32 quail per collection. Each bird was individually weighed. The blood sample was collected by cardiac puncture, collecting about 3 mL blood. The complete blood count was performed with 1 mL blood, using 20 μL of EDTA 5% for each mL of blood. The remaining volume was placed in a tube without anticoagulant to obtain serum after centrifugation. Then the birds were euthanized. The bursa of Fabricius, thymus, spleen and liver were weighed on a precision scale. It was calculated normal ratio of heterophil:lymphocyte (H/L) and it was measured the total area of 290 erythrocytes per age group. The images of the erythrocytes were obtained and analyzed by digital camera (Moticam 2500) coupled to the optical Zeiss microscope equipped with an image analysis system (Motic Images Plus Version 2.0). The serum was measured for concentrations of total protein, Aspartate Aminotransferase (AST), Alanine Aminotransferase (ALT), Gamma glutamyl transferase (GGT), Alkaline Phosphatase (ALP), triglycerides, total cholesterol, urea, uric acid and calcium by the automatic biochemical analyzer Mindray (BS-120) using commercial reagent kits (Labtest Diagnóstica S.A.®). First, it was applied to the groups the Shapiro-Wilk normality test through the statistical program BioEstat 5.0. Then, the comparison between two groups was made by t-test or the Mann-Whitney U. Finally, the comparison of more than two groups was taken by Tukey test or viii Kruskal-Wallis test at 5% significance level. Birds with 80 days of age showed an involution of the spleen, thymus and bursa of Fabricius. Young birds showed lower average values of packed cell volume, red blood cells and hemoglobin concentration. Furthermore, they showed red blood cells in larger size and concomitantly higher average values of mean corpuscular volume. Also, showed heterophils as the predominant leukocyte and consequently higher H/L. It is noteworthy that there appears to be a correlation in the number of circulating lymphocytes and weight of the lymphoid organs. Quails with 80 days of age showed higher average values of total serum protein, calcium and lipids. It was found a linear decrease of average values of ALP activity in quails between 7 and 80 days of age. We conclude that there are variations in hematological and biochemical parameters of Japanese quails in accordance with age. Therefore, the results of this study serve as a warning for the evaluation of hematological parameters of the specie, as these variations are physiological and should not be associated with diseases.